Improving the Care of People with Long-Term Conditions in Primary Care: Protocol for the Enhance Pilot Trial. Issue 1 (2015) - Healey, Emma L.; Jinks, Clare; Tan, Valerie A.; Chew-Graham, Carolyn A.; Lawton, Sarah A.; Nicholls, Elaine; Finney, Andrew G.; Porcheret, Mark; Cooper, Vince; Lewis, Martyn; Dziedzic, Krysia S.; Wathall, Simon; et al.
Background: Long-term conditions (LTCs) are important determinants of quality of life and healthcare expenditure worldwide. Whilst multimorbidity is increasingly the norm in primary care, clinical guidelines and the delivery of care remain focused on single diseases, resulting in poorer clinical outcomes. Osteoarthritis, and anxiety and/or depression frequently co-occur with other LTCs, yet are seldom prioritized by the patient or clinician, resulting in higher levels of disability, poorer prognosis, and increased healthcare costs. Objective: To examine the feasibility and acceptability of an integrated approach to LTC management, tackling the under-diagnosis and under-management of osteoarthritis-related pain and anxiety and/or depression in older adults with other LTCs in primary care. Design: The ENHANCE study is a pilot stepped-wedge cluster randomized controlled trial to test the feasibility and acceptability of a nurse-led ENAHNCE LTC review consultation for identifying, assessing, and managing joint pain, and anxiety and/or depression in patients attending LTC reviews. Specific objectives (process evaluation and research outcomes) will be achieved through a theoretically informed mixed-methods approach using participant self-reported questionnaires, a medical record review, an ENHANCE EMIS template, qualitative interviews, and audio recordings of the ENHANCE LTC review. Discussion: Success of the pilot trial will be measured against the level of the primary care team engagement, assessment of training delivery, and degree of patient recruitment and retention. Patient satisfaction and treatment fidelity will also be explored. ISRCTN registry number: 12154418.